Mechanism of Imprinting Process in the Ni-P Metallic Glass Films: A Molecular Dynamics Study - Tri Widodo Besar Riyadi; Ramaswamy Sivaraman; Alaa Mohammed Hussein Wais; Farag M. A. Altalbawy; Ulugbek Oybutaevich Khudanov; Dinesh Kumar Chaudhary (Advances in Materials Science and Engineering)
In this study, the molecular dynamics (MD) simulation was used to evaluate the role of imprinting temperature and the mold-cavity geometry on the imprinted Ni-P metallic glass (MG) films. Considering the outcomes of simulation, it was found that the tip-like and groove patterns showed different filling time for the imprinting process. At room temperature (300 K), the plastic deformation in the tip-like pattern was in a ring shape enclosing the mold, while the plastic deformation in the groove-pattern geometry was mainly localized at the wall of mold. Moreover, it was determined that the imprinting at high temperature (700 K) led to the shortening of pattern filling time and the decrease of loading force in both geometries. The strain concentration and localized plastic deformation were also removed in the high-temperature imprinting process. On the other hand, the unloading process at room temperature (300 K) improved the imprinting quality due to the lower elastic recovery.